Thermal blanketing by ivy (Hedera helix L.) can protect building stone from damaging frosts - Coombes, M; Viles, H; Zhang, H (Springer Nature, 2018)
The impact of plants growing on buildings remains controversial, especially for vulnerable historic walls and ruins requiring on-going conservation. English ivy (Hedera helix L.) can cause considerable damage where it is able to grow into deteriorating masonry, yet in some circumstances it may be protective. Here we focus on the potential of ivy to buffer damaging thermal cycles and frost events that can contribute to the deterioration of masonry materials. On limestone masonry test walls in central Southern England (Wytham near Oxford, UK), ivy foliage had a significant influence on stone-surface freezing regimes. Over two successive winters (2012/13 and 2013/14) the frequency of freezing events under ivy was reduced on average by 26%, their duration by 34% and their severity by 32%. A subsequent laboratory simulation showed that stone mass loss, surface softening, and textural development were all significantly reduced under an ‘ivy covered’ thermal regime. Cautious extrapolation indicates that ivy can reduce frost-driven granular-scale decay of limestone by the order of 30 g m−2 yr−1, depending on the local freezing regime. Whilst the capacity of ivy to cause damage should not be underplayed, vertical greenery can aid heritage conservation efforts by mitigating specific environmental threats.